2023
DOI: 10.1007/s10833-022-09476-0
|View full text |Cite
|
Sign up to set email alerts
|

Teacher attributions of workload increase in public sector schools: Reflections on change and policy development

Abstract: In education systems around the globe influenced by neoliberalism, teachers commonly experience reforms which emphasise local responsibility and accountability. Teachers additionally work within what has been described as an era of social acceleration and associated "fast policy", with a perceived increase in the pace of reform. In this article, we present data drawn from a large (N = 18,234) survey of Australian public-school teachers' work. Analysis of both quantitative and qualitative reports indicates a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
0
3
0
2
Order By: Relevance
“…Sin embargo, se ha mencionado en reiteradas ocasiones la sobrecarga laboral que implica el ejercicio docente, pues el profesorado, además de cumplir con su extensa jornada laboral, requiere trabajar en muchas ocasiones, en sus hogares (Allen et al, 2021), sacrificando tiempo destinado a la recreación y al fortalecimiento de vínculos familiares en pro de su perfeccionamiento profesional y de la mejora de sus prácticas educativas (Santiago, 2023). Estas percepciones del profesorado respecto al aumento de la carga de trabajo se hacen mayor en aquellos pertenecientes a escuelas públicas (Ogakwu et al, 2023;Stacey, McGrath-Champ & Wilson, 2023).…”
Section: Programa Psicoeducativo Aplicado En El Profesorado Como Meca...unclassified
See 1 more Smart Citation
“…Sin embargo, se ha mencionado en reiteradas ocasiones la sobrecarga laboral que implica el ejercicio docente, pues el profesorado, además de cumplir con su extensa jornada laboral, requiere trabajar en muchas ocasiones, en sus hogares (Allen et al, 2021), sacrificando tiempo destinado a la recreación y al fortalecimiento de vínculos familiares en pro de su perfeccionamiento profesional y de la mejora de sus prácticas educativas (Santiago, 2023). Estas percepciones del profesorado respecto al aumento de la carga de trabajo se hacen mayor en aquellos pertenecientes a escuelas públicas (Ogakwu et al, 2023;Stacey, McGrath-Champ & Wilson, 2023).…”
Section: Programa Psicoeducativo Aplicado En El Profesorado Como Meca...unclassified
“…Frente a esta problemática y considerando las insuficiencias en las políticas públicas para promover la mejora de la salud mental en las comunidades educativas, esta investigación estableció por propósito informar una intervención psicoeducativa en relación con la salud mental del profesorado de nivel escolar, para ayudar a minimizar los efectos adversos en los docentes que además son, en muchos casos, protagonistas de la contención emocional del estudiantado (Lee et al, 2023;Stacey, McGrath-Champ & Wilson, 2023;Granziera et al, 2022). Por lo anterior, este estudió estableció dos objetivos: (a) describir los niveles de depresión, ansiedad y estrés en un grupo de profesores y profesoras de nivel escolar; (2) informar una intervención psicoeducativa basada en el "Modelo de consulta" para promover la salud mental en el profesorado.…”
Section: Programa Psicoeducativo Aplicado En El Profesorado Como Meca...unclassified
“…Teaching is considered one of the most important professions around the world. Besides spending many hours per week in activities in the classroom, it is common for teachers to perform extracurricular activities (e.g., setting up and correcting exams and being school coordinators), which leads to a high workload [1][2][3]. Extracurricular activities are usually carried out during weekends, which decreases the time for recreational activities and family [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, teachers report difficulty in decreasing their working hours due to their demands to improve the teaching quality and the expectations of society [5]. It should be highlighted that almost 90% of teachers in public schools reported an increase in overall hours over the past years [1]. Previous studies have demonstrated that a high workload decreases well-being and affects physical and mental health, such as an increase in stress levels [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In many parts of the world, the urgency and scale of the teacher shortage has meant greater attention to the attraction of people to the profession and within-school working conditions as explainers of workforce performance and retention, e.g., [6,7]. However, initiatives to attract and retain teachers mean little if teachers cannot afford to live within commuting distance of their workplace.…”
Section: Introductionmentioning
confidence: 99%